Becoming minor: Mapping new territories in occupational science. Issue 4 (2nd October 2017) - Barlott, Tim; Shevellar, Lynda; Turpin, Merrill
ABSTRACT: This paper draws upon the poststructural work of Deleuze and Guattari to outline a framework for analyzing social formations in a way that is acentred from the individual. The concepts of the major and minor, becoming minor and the rhizome provide a useful framework for scholars and practitioners to engage in affirmative political modes of thought, challenge dominant discourses and seek transformative processes. The major are the dominant things in the social world (both human and non-human, physical and non-physical) that are established, clearly understood and considered normal. The minor is the site of difference, that which does not align with the norm. The major seeks to categorise and stratify the minor, oppressing the minor and limiting its potential. In order to resist the capture of the major and pursue social transformation, Deleuze and Guattari introduced the concept of becoming minor, a collective process of resistance to categorical/normative identities. The process of becoming minor is illustrated through the concept of the rhizome, a non-hierarchical figuration of the interrelated and continually changing nature of things. The rhizome is a useful tool for analyzing and articulating social formations, and invites a deeper understanding of the flows that are entwined with occupation. Mapping cartographies of rhizomatic processes may open up creative possibilities for occupational science and new ways of thinking about occupation beyond the individual.